Quality evaluation and price discrimination of jasmine-scented tea - Zhang Jun; Gong Shuying; Tang Desong; Zhang Yingbin; Chen Meili (浙江大学学报. 农业与生命科学版)
Jasmine-scented tea is a mainstream product of scented tea, which is very popular in Chinese northern tea market. Until nowadays, tea quality evaluation still mainly depends on the sensory assessment, which is potentially affected by individual preference and physical and mental conditions of tasters. It is necessary to search for objective and quantifiable methods for quality evaluation and discrimination. Factor analysis and discriminant analysis are statistical methods widely used in natural science, medicine, economics, sociology and many other fields. There have been some researches about application of these two methods in evaluating tea quality or discriminating the locality, variety and grade of tea. In this paper, factor analysis and discriminant analysis were used for quality evaluation and price discrimination of jasmine-scented tea. Compared with the sensory evaluation, extraction is an usual method to get tea liquor for tea quality research, which is considered to be a time and energy consuming method. In the present paper, brewing method for sensory analysis was introduced in the price discrimination study, aiming at simplifying the method for preparing tea liquor.One hundred and twelve samples of jasmine-scented tea with price ranging from 28 to 3 000 Yuan RMB per kilogram were purchased from tea market or supplied by tea companies of Wuyutai, Zhangyiyuan, Yuanchanghou and Jinghua. The tea liquor was prepared by brewing and extracting methods respectively. Brewing method for sensory analysis, 3.0 g jasmine-scented tea was infused with 150 mL freshly boiled water for 5 min and then filtered while hot. The concentrations (mg/mL) of 13 main chemical components were measured. Total extracting method, the tea liquor was prepared according to the method of China national standard GB/T 8312—2002. Extracting 3.0 g jasmine-scented tea powder with 450 mL boiled water for 45 min in boiling water bath and shaking it in every 10 min. The liquor was pressure filtered while hot and diluted with distilled water to 500 mL when cooled. The contents (%) of 13 main chemical components were measured. Concentrations and contents of polyphenols, amino acids and water soluble extract were determined by the methods of China national standard GB/T 8313—2002, GB/T 8314—2002 and GB/T 8305—1987, respectively. While concentrations and contents of caffeine, gallic acid (GA) and the composition of catechins including gallocatechin (GC), epigallocatechin (EGC), catechin (C), epicatechin (EC), epigallocatechin gallate (EGCG), gallocatechin gallate (GCG), epicatechin gallate (ECG), catechin gallate (CG) were determined by high performance liquid chromatography (HPLC). Factor analysis and discriminant analysis were carried out based on the 32 variables using SPSS 16.0 for Windows.The models for quality evaluation and price discrimination of jasmine-scented tea samples were established by factor and discriminant analysis based on the data obtained from brewing and extracting methods. For brewing and extracting methods, 5 factors with cumulative variance of 91.825% and 93.858% were obtained along with factor analysis, and 5 factor score functions and 1 comprehensive evaluation function were obtained. Three Bayes discrimination functions were obtained along with discriminant analysis. For the two methods, recognition accuracy of back substitution was 85.7% and 83.9%, respectively; meanwhile the recognition accuracy of the cross-validation was 84.8% and 81.3%, respectively. On the whole, the discrimination results are satisfactory and the brewing method for sensory analysis is better.